The Impacts And Challenges Emanating As Consequence From The “Black, Grey, And White (BGW) List” On Port State Control In The Asia-Pacific Region - Hidayah, Ferro (Dinasti Research, 2024)
This study aims to describe the understanding of the flag-state administration, recognized organizations, and seafarers onboard regarding the implementation of the port State control for dealing with the impacts and challenges resulting from the results of inspections by port State control. The research relies on qualitative analysis. The primary data was obtained from personal experience and informal discussions with Port State Control Officers (PSCO) of Indonesia and related parties to this research. The secondary data was gathered from National regulations relating to the ratification of IMO conventions, the annual port State control reports in the Asia-Pacific region, publications of organization, sources of documentation, journal references, and various works and literature supporting this research's objectives. The ultimate responsibility of keeping the ship in compliance with international standards lies with the shipowner, flag States, and other relevant industry players. The